Performance Indicators in Young Elite Beach Volleyball Players - Pérez-Turpin, José Antonio; Campos-Gutiérrez, Luis María; Elvira-Aranda, Carlos; Gomis-Gomis, María José; Suárez-Llorca, Concepción; Andreu-Cabrera, Eliseo (Frontiers in Psychology, 2019)
Purpose: The purpose of this study was to analyze the technical and tactical behavior of female and male beach volleyball professionals and discover any gender differences. Method: 40 teams from from the under-18, under-20, under-21, and under-22 from semifinals and finals of the 2016 World Championships and the 2016 European Championship were analyzed. The sample was composed of 69 sets. The variables studied included: effectiveness serve, blocks, types of colocation, and performance of the attacks and blocks. T-Student and Mann Whitney U tests were used to analyze specific differences between categories. Results: Significant differences (P <0.05) in the pass performance, forearm pass in mens (from 78.2% to 49.1%), and overhand pass in mens (from 12.2% to 40.45%). In addiction, in women forearm pass (from 88.5% to 76.3%), and overhand pass in women (from 1.2% to 9.35%). No significant differences in the effectiveness of attack. Conclusions: Tactical considerations and gender-specific differences in technical and physical variables may be important for training.